The use of the kangaroo method in Neonatal Intensive Care Units (Research, Society and Development, 2021)
Prematurity is a public health problem that requires the need for hospitalization of the newborn (NB) in Neonatal Intensive Care Units (NICU), however, generates a premature separation between mother and baby, being considered by mothers a devastating and traumatic moment, in addition to changing the dynamics and family routine. This study aims to discuss from literature findings the use of the kangaroo method in neonatal intensive care units focusing on its benefits. This is a descriptive study, of the integrative literature review type, of qualitative nature, the search for articles was performed with the aid of the LILACS, SciELO, BDENF, via BVS, and Scholar Google databases. The articles were collected in the period April 2021.  The descriptors "Kangaroo Method" and "Neonatal Intensive Care Unit" and "Premature Newborn" were used, crossed with the boolean operator "AND", located in the list of Descriptors in Health Sciences (DECs). After applying the eligibility criteria, 13 studies were left that fit the research objective. The use of the kangaroo method comprises a new model of care that includes the family in the treatment of the newborn, aiming to humanize care. It is concluded that the benefits of this method are broad, contributing significantly to the development of the NB in several aspects, besides promoting a greater bond between mother and baby.